Natural Orchid Diversity and Its Conservation Strategies in Wonosobo Aqua Biodiversity Park - Dapala, Oktomarios; Siman, Suwadji; Nanda, Nugraha Satya (Advances in Tropical Biodiversity and Environmental Sciences, 2022)
This study aims to determine the diversity of natural orchids and to design a strategy for preserving natural orchids in the KEHATI AQUA Park, Wonosobo. The data sought in this study were the type, number, diversity of orchids, and questionnaire respondent data. The results showed that there were three types of natural orchids in KEHATI AQUA Wonosobo Park, namely Dendrobium crumenatum, Eria retusa,  and Liparis sp. Overall, the total number of orchids found was 487 individuals. The three types of orchids found were epiphytic orchids found on 6 types of host trees. Based on the questionnaire respondents' data which was carried out by a SWOT analysis, there were several strategies designed, namely optimizing the land for orchid conservation, utilizing existing facilities in cultivation ( green house ), increasing the types of orchids to be cultivated and caring for and maintaining existing vegetation for orchid host trees, making policies aimed at preserving orchids and establishing cooperation with the orchid conservation community. The conclusion of this study is that there are 3 types of natural orchids in KEHATI AQUA Wonosobo Park, namely Dendrobium crumenatum with an INP value of 1.04 , Eria Retusa with an INP value of 0.87, and Liparis sp with an INP value of 0.09, a diversity index value of 0.72, an evenness index value of 0.66 and the species richness index value of 0.32 and the alternative strategy used in the conservation of natural orchids in the KEHATI AQUA Park Wonosobo is the SO strategy or a strategy that is made to take advantage of all strengths to seize and take advantage of opportunities as much as possible.